Coconut shell, coconut shell activated carbon and beta-silicon carbide reinforced polymer composite: An alternative dielectric material for wireless communication application - Been Seok Yew; Martini Muhamad; Saiful Bahri Mohamed; Fwen Hoon Wee (Bulletin of Electrical Engineering and Informatics, 2020)
The effect of coconut shell (CS), coconut shell activated carbon (CSAC) and beta-silicon carbide (β-SiC) in polymer composites was investigated. Elemental composition, surface morphologies and structural analyses of the fillers were performed using carbon, hydrogen, nitrogen and sulfur (CHNS) analyser, scanning electron microscope (SEM) and X-ray Diffractometer (XRD). The dielectric properties of the composites were measured using open-ended coaxial line method. CS and CSAC fillers had positive influence on the dielectric properties (ε’, ε” and σ) of the polymer composites, contributed by the orientation polarizations arises from polar nature of the amorphous CS and CSAC fillers. β-SiC filler had insignificant influence on the dielectric properties of the polymer composites due to its single polarization of the crystalline structure filler. This finding is in agreement with XRD patterns of CS and CSAC fillers that revealed the presence of amorphous structure with broad diffraction peaks that were detected at 2ϴ=22.236°, 34.8604° and 2ϴ=23.985° and 44.015°, respectively. The amorphization structure in the polymer composites allows the displacement and conduction currents that were induced from electric field to flow through the polymer composites when subjected to electromagnetic energy, thus increased the dielectric properties of the composites.